2020
DOI: 10.1136/jech-2020-213754
|View full text |Cite
|
Sign up to set email alerts
|

Associations in physical activity and sedentary behaviour among the immigrant and non-immigrant US population

Abstract: BackgroundImmigrants are at a higher risk of poor mental and physical health. Regular participation in physical activity (PA) and low levels of sedentary time are beneficial for both these aspects of health. The aim was to investigate levels and trends in domain-specific PA and sedentary behaviour in the US. immigrant compared with non-immigrant populations.MethodsFrom the 2007–2016 National Health and Nutrition Examination Survey (NHANES), a total of 25 142 adults (≥18 years) were included in this analysis. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The results of this study showed that among a number of US immigrant subgroups, the proposed model was only significant in some groups, including male, Mexican American, Non-Hispanic White, and lower education and income. These results were generally in line with the findings of other relevant literature showing that the relationships between duration of United States residence and health-related variables may vary depending on sociodemographic or SES factors (Dawson et al, 2005;Kakinami et al, 2018;Kim et al, 2020). Therefore, this study suggests that adverse socioeconomic profile (low education and income) may be a risk factor for obesity and physical inactivity within the US immigrants.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that among a number of US immigrant subgroups, the proposed model was only significant in some groups, including male, Mexican American, Non-Hispanic White, and lower education and income. These results were generally in line with the findings of other relevant literature showing that the relationships between duration of United States residence and health-related variables may vary depending on sociodemographic or SES factors (Dawson et al, 2005;Kakinami et al, 2018;Kim et al, 2020). Therefore, this study suggests that adverse socioeconomic profile (low education and income) may be a risk factor for obesity and physical inactivity within the US immigrants.…”
Section: Discussionsupporting
confidence: 92%
“…While NHWs had significantly higher mortality across disease classes compared to VietAms, NHW mortality decreased for nearly every leading cause over the study period. Our data supports the possibility of the "Healthy Immigrant Effect" described in the literature; immigrants have overall better health, but this advantage attenuates with increased length of residency [21][22][23][24][25]. Previous studies proposed that the selectivity of the immigration process explains the overall better health of immigrants.…”
Section: Plos Onesupporting
confidence: 88%
“…Age groups were classified as young (18-35 y), middle aged (36-55 y), and older adults (>55 y). 20 In race/ethnicity groups, Mexican American, other Hispanic, non-Hispanic white, non-Hispanic black, and other race (including multiracial) were included. Annual household income was divided into 4 groups: <$25,000; $25,000 to $45,000; $45,000 to $75,000; and >$75,000.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…Researchers, public health educators, and clinicians may need a comprehensive understanding of the secular tendencies of immigrants' physical activity to see the temporal changes in the distribution of health correlates over time. Recently, Kim et al 20 investigated levels and trends in recreational and transit-related physical activity (ie, walking/biking to work and/or for errands, also called transportation physical activity) in US immigrant populations compared with nonimmigrant populations. They reported that young adult immigrants (18-35 y) exhibited lower levels of recreational physical activity, whereas higher levels of recreational physical activity and transit-related physical activity were found among older immigrants (>55 y) compared with USborn individuals.…”
mentioning
confidence: 99%